Ways of being a teacher in PIBID Social Sciences (2020-2022):: experiences in training, research, and diversity in education (Simbiótica. Revista Eletrônica, 2024)
This article presents results from a case study analyzing the PIBID-FCS-UFG (2020-2022), situated within the scope of the Institutional Program for Teaching Initiation Scholarships (PIBID) at the Federal University of Goiás, serving the Bachelor's degree in Social Sciences. The aim was to reflect on the Program's impacts as a possible guiding wisp to articulate dimensions of teaching and research, which were verified through narrative biographies and documentary analysis. In addition to teaching initiation and the development of skills for research and extension, the PIBID-FCS-UFG has been oriented towards engaged training in the issues of differences in education - such as gender, race, ethnicity, sexuality, generation, among others -, presenting various initiatives for this purpose. The results also indicate how the program opens possibilities for research development, contributing to the formation of teacher-researcher profiles, by guiding their actions through emancipatory formative processes.
Keywords: PIBID; teacher training; differences; research